2017
DOI: 10.1155/2017/7269147
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Presentation of Isolated CNS Posttransplantation Lymphoproliferative Disorder

Abstract: Posttransplantation lymphoproliferative disorder (PTLD) is a recognized and extremely morbid complication of solid organ transplantation, but central nervous system involvement, particularly in isolation, is rare. There are no standardized treatment strategies for PTLD, though commonly used strategies include reduction of immunosuppression, chemotherapy, rituximab, radiation, and surgery. We present a case of an unusual morphologic variant of primary central nervous system PTLD with successful response to ritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…One HTLV-1 non-carrier in our study developed PTLD (EBV+) in the brain after renal transplantation instead of ATL. Immediate diagnosis and subsequent treatment, including rituximab plus HDAC or HD-MTX, did not improve PTLD in the brain according to a review by Nagel et al ., 37 a previous report of PTLD in the brain, 15 , 38 and previous reports on PTLD treatments 39 - 46 . Thus, careful follow-up may also be necessary to detect the development of PTLD after renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…One HTLV-1 non-carrier in our study developed PTLD (EBV+) in the brain after renal transplantation instead of ATL. Immediate diagnosis and subsequent treatment, including rituximab plus HDAC or HD-MTX, did not improve PTLD in the brain according to a review by Nagel et al ., 37 a previous report of PTLD in the brain, 15 , 38 and previous reports on PTLD treatments 39 - 46 . Thus, careful follow-up may also be necessary to detect the development of PTLD after renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…ITSS within intracranial lesions is thought to be the result of tumoral microhemorrhage, necrosis, and angiogenesis. A few cases of significant hemorrhage causing acute neurological symptoms, attributed to PCNS-PTLD, have been reported [20 , 51] . Hemorrhage and necrosis are known to increase following treatment, and increased ITSS is expected ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 A PRISMA flowchart of our screening and review process. [2 , 3 , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , 38 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [51] , [52] , [53] , [54] , 57 , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , …”
Section: Methodsunclassified
“…[ 7 ] Morris J, et al reported a patient treated with RI, rituximab and cranial radiation. [ 8 ] Arita H, et al presented two cases of P-PTLD treated with RI plus steroids and surgery plus irradiation separately. [ 9 ] Velvet AJJ, et al reported a case treated with RI, craniotomy, radiotherapy and rituximab.…”
Section: Discussionmentioning
confidence: 99%